Institutionalization Process: what changes in the life of the elder? - Silva, Ana Carolina Fernandes (2017)
This is a reflection aiming at understanding what changes the institutionalization process brings to the life of the elder, and identify the role of the family and of the state regarding elder care in the context of an Elderly Long Permanence Institution (ELPI). Population aging in Brazil is increasing, and that happens in a context of social, economic and cultural change, in the value system and in new family arrangements. The search for ELPI, in the face of this demographic and social perspective, is increasing, and represents a new alternative of housing for the elderly. It stands out that one of the factors that culminate in the institutionalization of the elderly is the reduction of their social support network as they age. In the daily life of the institutionalized elderly, ELPIs should develop activities that enable the elderly person to exchange knowledge and experiences.